Thermal degradation of mango (Mangifera indica) wood sawdust in a nitrogen environment: characterization, kinetics, reaction mechanism, and thermodynamic analysis. Issue 22 (12th April 2021) - Sharma, Ajay; Mohanty, Bikash
Abstract : Kinetic and thermodynamic data were extracted from the pyrolysis of waste MIW sawdust for design and operations of an efficient pyrolysis system. Abstract : For better utilization of 11 million tonnes of Mangifera indica wood (MIW) sawdust produced annually in India, the present study was planned for its characterization followed by determination of its pyrolysis kinetics from TGA data under a N2 atmosphere. The characterization process included proximate-, ultimate-, biopolimeric components-, and heating value-analysis, as well as TG/DTG analysis. The distributed activation energy (DAE)- and Starink-methods were implemented on non-isothermal thermograms to compute the isoconversional values of activation energy for the pyrolysis of MIW. Further, the reaction mechanism for the pyrolysis of MIW was predicted using the Coats–Redfern (C–R) model-fitting method. Two distinct pyrolysis regions, region-I from 0.05–0.5 and region-II from 0.51–0.7, were observed in the complete conversion ranges. The estimated activation energy for region-I ranged from 143.03 to 176.46 kJ mol −1 with an average value of 157.12–157.97 kJ mol −1 and that of region-II varied between 143.03 and 161.68 kJ mol −1 with an average of 151.51–152.45 kJ mol −1 . The one-dimensional diffusion model (D1 ) followed by the five and a half reaction order model (F5.5 ) were recommended to describe the pyrolysis reaction mechanism of MIW for the two above regions, respectively. Further, the activation energies obtained via the DAE and Starink methods were used for the computation of thermodynamic parameters such as frequency factor, and change in-enthalpy, -entropy, and -Gibbs free energy.